Analytical Solutions of Dynamic Extension Problem of Mode III Semi-Infinite Crack Subjected to Moving Increasing Loads - Lu, Nian-Chun; Xiang, Qian; Hao, Guo-Dong (Asian Journal of Chemistry, 2014)
Dynamic extension problem of mode III semi-infinite crack was investigated by means of the theory of complex variable functions, which can be facilely transformed into Riemann-Hilbert problems. Analytical solutions of stress, displacement and stress intensity factor under the conditions of moving increasing loads Px2/t2 and Pt3/x2, respectively, are very easily obtained using the ways of self-similar functions.